A 90th birthday tributeAnthony D. King: an appreciation. (4th May 2022) - Kusno, Abidin
ABSTRACT: The work of Anthony D. King is among the very best of recent urban and global studies. This essay is a tribute in appreciation of Tony King as a scholar, mentor, and friend. It discusses some of his major contributions in the fields of global cities research, colonial and postcolonial urban studies, as well as his views on knowledge and positionality in relation to the location within which he is embedded. It is a mix of anecdotal and analytical notes written as a tribute to a great teacher who has reached a milestone - 90 years old.